The Effect of Communication Channels on Promise-Making and Promise-Keeping - Julian Conrads; Tommaso Reggiani (Institute for the Study of Labor (IZA), 2014)
This paper investigates the effect of different communication channels on promise-making and promise-keeping in a helping situation. Four treatments differ with respect to the communication channel employed to solicit unincentivized cooperation, i.e., face-to-face, phone call and two different sorts of computer-mediated communication. The less anonymous (face-to-face, phone) the interpersonal interaction is due to the different communication channels, the higher the propensity of an agent to make a promise. Treatment effects, however, vanish if we then look at the actual promise-keeping rates across treatments as more anonymous channels (computer-mediated) do not perform relatively worse than more direct channels.
Keywords: D02; D83; C91; 330; promises; communication; experimental economics; organizational behavior; behavioral ethics